2011
DOI: 10.1007/s10530-011-9977-y
|View full text |Cite
|
Sign up to set email alerts
|

Strong regeneration ability from rhizome fragments in two invasive clonal plants (Solidago canadensis and S. gigantea)

Abstract: The two rhizomatous perennials Solidago canadensis and S. gigantea belong to the most widespread alien plants in Europe. Anecdotal observations suggest that they disperse also by rhizome fragments. For testing their resprouting ability, rhizome fragments of different sizes from both species were buried at four different soil depths (0, 5, 10 and 20 cm, respectively) in a common garden. Rhizome fragments of S. canadensis ranged 3-6 cm in length, those of S. gigantea 5-20 cm in length. Resprouting plants were ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
36
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 35 publications
5
36
1
2
Order By: Relevance
“…The giant goldenrod reproduces through viable, hair-equipped and wind-dispersed seeds (Weber and Jacobs 2005), and vegetatively through rhizomes, and it is the most dangerous plant-invader of American origin. It has been shown that goldenrod plants are capable of producing new shoots from rhizome fragments buried as deep as 20 cm below ground surface (Weber 2011). The introduced populations of giant goldenrod produce more shoots by clonal growth than native populations.…”
Section: Introductionmentioning
confidence: 99%
“…The giant goldenrod reproduces through viable, hair-equipped and wind-dispersed seeds (Weber and Jacobs 2005), and vegetatively through rhizomes, and it is the most dangerous plant-invader of American origin. It has been shown that goldenrod plants are capable of producing new shoots from rhizome fragments buried as deep as 20 cm below ground surface (Weber 2011). The introduced populations of giant goldenrod produce more shoots by clonal growth than native populations.…”
Section: Introductionmentioning
confidence: 99%
“…Their success is due to strong colonization ability-single plants grow rapidly up to 2 m height and can produce up to ten thousand light, winddispersed, seeds (Kabuce and Priede 2010). Moreover, they propagate extremely efficiently by rhizomes, the primary proliferation route in stable populations (Hartnett and Bazzaz 1985;Weber 2011). Goldenrods also produce allelopathic compounds, effectively inhibiting the growth of other plants (Abhilasha et al 2008;Callaway and Aschehoug 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas cutting methods have been reported to successfully hamper invasions (Delbart et al 2012;Wittenberg and Cock 2001;Levy et al 2011), they harvest substantial amounts of invasive plant material. In species capable of vegetative reproduction, plant fragments represent vegetative propagules that can establish new populations and enhance invasion (Bímová et al 2003;Eriksson 1993;Weber 2011). In this context, it is important to consider the fate of the plant material harvested in cutting campaigns and that land managers need a disposal method that is legal, cost effective and efficient in reducing further invasions (De Waal 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, despite the number of ornamental plant invaders found along roads and railways, as well as in other places commonly managed by mowing and shredding, little is known about the vegetative regeneration capacity of shredded invasive plant material, and the risk it represents for the environment (but see De Waal 2001;Song et al 2013). Rhizomatous and/or woody ornamental plants often show good vegetative reproduction (Davies et al 1994).The vegetative fragment size and the cutting period may have considerable impact on vegetative regeneration capacity (De Waal 2001;Cordazzo and Davy 1999;Weber 2011;Lin et al 2012). In the present study, we focused on five ornamental widespread invaders in Western Europe that are likely to be managed by cutting techniques (Levy et al 2011) (Randall and Marinelli 1996).…”
Section: Introductionmentioning
confidence: 99%